Soil Properties Control Microbial Carbon Assimilation and Its Mean Residence Time - Ali, Rana Shahbaz; Poll, Christian; Kandeler, Ellen (Frontiers in Environmental Science, 2020)
Microbial assimilation and stabilization of soil organic carbon (SOC) is an important process in global carbon cycling. For an improved understanding of climate-induced changes in ecosystem C dynamics, it is important to know the group-specific turnover of microbial C. Consequently, we wanted to answer the questions if fungi store newly assimilated C longer than bacteria and if climatic and edaphic properties of different regions affect microbial C assimilation and its subsequent release. This study presents results from a 112-day long field experiment where endogenous soil microorganisms were labelled with 13C labelled glucose to follow the dynamics of newly assimilated C in two study regions (Kraichgau and Swabian Alb). Whereas microbial assimilation of newly added C was higher in Kraichgau than in Swabian Alb, the opposite result was obtained for the mean residence time (MRT) of microbial biomass C (76 days in Kraichgau and 93 days in Swabian Alb). The accelerated turnover rates of microbial C in the warmer soils of Kraichgau with lower clay content might be an important mechanism explaining the differences in SOC content between both regions. Gram-positive bacteria assimilated more 13C-glucose into their biomass than fungi and the MRT of C was higher in bacteria as compared to fungi in both regions. Beside these dynamic substrate utilization strategies, we could proof cross feeding by gram-negative bacteria. Carbon MRT in fungi was region specific and was best represented by a two-pool model; the initial MRT ranged between 5 to 39 days and was, in the end, higher than 4 years. This provides evidence of a possible shift in fungal community composition; fast growing fungi dominant in the early phase and internal redistribution of C in the second phase of decomposition. Our study identified microbial group and region specific MRT of freshly assimilated C as an important parameter, which might help to explain the commonly found variation in soil respiration and SOC stabilization.